2014
DOI: 10.1186/1471-2458-14-484
|View full text |Cite
|
Sign up to set email alerts
|

What have we learned about communication inequalities during the H1N1 pandemic: a systematic review of the literature

Abstract: BackgroundDuring public health emergencies, public officials are busy in developing communication strategies to protect the population from existing or potential threats. However, a population’s social and individual determinants (i.e. education, income, race/ethnicity) may lead to inequalities in individual or group-specific exposure to public health communication messages, and in the capacity to access, process, and act upon the information received by specific sub-groups- a concept defined as communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
157
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(170 citation statements)
references
References 64 publications
11
157
0
2
Order By: Relevance
“…In terms of outbreak information source, the television and radio were found to be the most utilized among the respondents regardless of socio-demographic factors. Recent studies on outbreak information dissemination had reported traditional media channels to still be the main source of information, with minimal health information exchanged on social media [43][44][45][46]. Our findings are also congruent with the study conducted by Vijaya et al [17] where the authors found that majority of the respondents depended on the television and printed media for timely and accurate information during the SARS outbreak in Singapore.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of outbreak information source, the television and radio were found to be the most utilized among the respondents regardless of socio-demographic factors. Recent studies on outbreak information dissemination had reported traditional media channels to still be the main source of information, with minimal health information exchanged on social media [43][44][45][46]. Our findings are also congruent with the study conducted by Vijaya et al [17] where the authors found that majority of the respondents depended on the television and printed media for timely and accurate information during the SARS outbreak in Singapore.…”
Section: Discussionsupporting
confidence: 90%
“…Although the reasons for these findings are not clear, similar results were reported during the H1N1 influenza pandemic in 2009 (14). Trust in public health officials, information-seeking behaviors, sources of information, frequency of media exposure, knowledge, and worry related to the outbreak were all highlighted determinants of documented disparities in uptake of recommended behaviors.…”
Section: Discussionsupporting
confidence: 64%
“…Their findings showed that the use of microblog or Weibo in China was positively associated with public awareness of a series of food safety incidents and factual awareness, in addition to preventive actions regarding food risks. However, in the case of infectious disease outbreaks, the impact of using SNSs on people's attitudes and behaviors has been largely overlooked (Lin, Savoia, Agboola, & Viswanath, 2014). Given that SNSs have been recognized as useful communication tools to raise awareness during an infectious disease outbreak (Chew & Eysenbach, 2010;Ding & Zhang, 2010;Liu & Kim, 2011), it is reasonable to assume that communication via SNSs of diseaserelated information influences people's perceptions, concerns, and behaviors in relation to the outbreak.…”
Section: Linking Sns Communication To Cognitive Characteristics and Pmentioning
confidence: 99%